Signature of the Brazil-Malvinas confluence in the isotopic composition of planktonic foraminifera from core top sediments - Chiessi, Cristiano Mazur; Ulrich, Shannon; Mulitza, Stefan; Pätzold, Jürgen; Wefer, Gerold (Anuário do Instituto de Geociências, 2006)
Abstract